Outdoor culture system realizing water circulation - WU SUJUAN; GUO YUEQIANG; CHEN WEIJING; CHEN QIUJU (2016)
The invention discloses an outdoor culture system realizing water circulation. The system comprises a pond and is characterized in that multiple aeration devices are arranged in the pond at intervals; a water treatment device is arranged at one end of the pond; a feeding device is arranged in the middle of the pond and comprises a storage barrel; a control valve is arranged below the storage barrel; an ejection device capable of ejecting materials in a feeding plate out of a discharging base is arranged on a floating platform; a scraping plate mechanism capable of collecting materials at the front end of the feeding plate to the rear side of the feeding plate is arranged on the ejection device; an oxygenation device is arranged at the other end of the floating platform. The outdoor culture system aims to overcome defects in the prior art, is simple in structure, can guarantee the content of oxygen in water and the water quality condition effectively and has a good culture effect, good bait dispersity during f